PRE-RESTORATION INVESTIGATIONS OF THE BASARABI CHALK MONUMENT DIAGNOSIS, TREATMENT AND IMPLICATIONS - Daniela Turcanu-Carutiu; Rodica-Mariana Ion (European Scientific Journal, ESJ, 2014)
This paper will sumarize several important aspects of the material research of chalk stone monument that is affected by various weathering/decay processes. Diagnosis of materials on monument should offer the necessary informations about the nature (genesis, composition) of materials and their states - intact and/or altered state. Detection of the major damage processes located on the studied monument can elucidate what are the factors contributing to the damage. Depending of the above results, will be established the managing restoration steps: selection of methodology of research, sampling strategy, analytical procedures and the time issue. Atmospheric pollution and acid deposition materials are recognized as the most important and common causes of decay the heritage monuments. Studies on chemical-mineralogical-physical changes in Basarabi chalk monument caused by weathering will also make a part of the paper. Discovered on 1957, the Basarabi – chalk church is one of the most impressive archaeological sites of Europe, consisting of churches dated from 9th - 11th century. Situated in the cliff of a chalk stone hill, this church is built from amorphous calcium carbonate and is very sensitive to humidity, frost, salts etc. The studies called ‘pre-restoration material investigation’ is in fact, ‘in-between two interventions’ – past one and future one. Only our deep understanding of these changes, together with recent material properties and their possible future development can make the material investigation of stone monuments a strong tool that improves the restoration itself.